Biomarkers of muscle damage and oxidative stress and biomechanical responses of two different advanced footwear technology shoes to a 60-min running test in competitive long-distance runners - Alda-Blanco, Alejandro; González-Mohíno, Fernando; González-Ravé, José María; Santos-Concejero, Jordan (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to analyse the influence of Advanced Footwear Technology (AFT) on biomechanical, muscle damage, metabolic and oxidative stress markers in experienced long-distance runners.MethodsUsing a counter-balanced randomized experimental design with twelve tier 3 male runners, two AFTs were tested: Cloudboom Strike (CS) and Cloudboom Echo 3 (CE). All participants completed, in both conditions, a graded exercise test (GXT) to determine the VT1, followed by a prolonged effort test (60-min) at an intensity 10% above VT1. Finally a GXT to exhaustion to assess the changes in biomechanical parameters in a fatigued state was performed. 24-h before and after each visit, blood samples were drawn for muscle damage, metabolic and oxidative stress determination.ResultsCreatin kinase (CK) increased post-visit in both CS and CE (p = 0.026; ES = 0.69 and p = 0.018; ES = 0.59; respectively). However, no other significant differences pre- and post-visit were found in lactate dehydrogenase (LDH), Interleukin-6 (IL-6), alanine aminotransferase (ALT), cortisol or total antioxidant status (TAS) in either the CS or CE conditions. There were no differences between conditions in any of the biomarkers measured, although participants perceived lower DOMS post-24 h with the CS model (p = 0.016; ES = 0.71). We found no shoe × time interaction in any biomechanical parameter evaluated during the prolonged effort or any variable at any speed stage between footwear conditions in the GXT to exhaustion.ConclusionAccording to our results, both the Cloudboom Strike and the Cloudboom Echo 3 models appear to provide minimal biomarker responses under these conditions after a 60-min treadmill run, regards to reducing muscle damage, oxidative and metabolic stress, soreness, and inflammation. This indicates attenuated biomarker responses when compared to previous studies with traditional footwear.